Hormones induce the formation of luminal-derived basal cells in the mammary gland - Song, Wenqian (Cell Res, 2019)
In the mammary gland, it is widely believed that the luminal cells are unipotent after birth, contributing only to the luminal compartment in normal development. Here, by lineage tracing, we uncovered an unexpected potential of luminal cells that can give rise to basal cells during pregnancy. These luminal-derived basal cells (LdBCs) persisted through mammary regression and generated more progeny in successive rounds of pregnancies. LdBCs express basal markers as well as estrogen receptor α (ERα). In ovariectomized (OVX) mice, stimulation with estrogen and progesterone promoted the formation of LdBCs. In serial transplantation assays, LdBCs were able to reconstitute new mammary glands in a hormone-dependent manner. Transcriptome analysis and genetic experiments suggest that Wnt/β-catenin signaling is essential for the formation and maintenance of LdBCs. Our data uncover an unexpected bi-potency of luminal cells in a physiological context. The discovery of ERα(+) basal cells, which can respond to hormones and are endowed with stem cell-like regenerative capacity in parous mammary gland, provides new insights into the association of hormones and breast cancer.